Pentoxifylline and electromagnetic field improved bone fracture healing in rats - Atalay Y; Gunes N; Guner MD; Akpolat V; Celik MS; Guner R (Dove Medical Press, 2015)
Yusuf Atalay,1 Nedim Gunes,2 Mehmet Dervis Guner,3 Veysi Akpolat,4 Mustafa Salih Celik,4 Rezzan Guner21Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Afyon Kocatepe University, Afyonkarahisar, 2Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Dicle University, Diyarbakir, 3Department of Orthopedics, Medicana Hospitals, Ankara, 4Department of Biophysics, Faculty of Medicine, Dicle University, Diyarbakir, TurkeyBackground: The aim of this study was to evaluate the effects of a phosphodiesterase inhibitor pentoxifylline (PTX), electromagnetic fields (EMFs), and a mixture of both materials on bone fracture healing in a rat model.Materials and methods: Eighty male Wistar rats were randomly divided into four groups: Group A, femur fracture model with no treatment; Group B, femur fracture model treated with PTX 50 mg/kg/day intraperitoneal injection; Group C, femur fracture model treated with EMF 1.5±0.2 Mt/50 Hz/6 hours/day; and Group D, femur fracture model treated with PTX 50 mg/kg/day intraperitoneal injection and EMF 1.5±0.2 Mt/50 Hz/6 hours/day.Results: Bone fracture healing was significantly better in Group B and Group C compared to Group A (P<0.05), but Group D did not show better bone fracture healing than Group A (P>0.05).Conclusion: It can be concluded that both a specific EMF and PTX had a positive effect on bone fracture healing but when used in combination, may not be beneficial.Keywords: bones, electromagnetic fields, fracture healing, phosphodiesterase inhibitor, pentoxifylline, rats